1993
DOI: 10.1006/jfan.1993.1025
|View full text |Cite
|
Sign up to set email alerts
|

On Certain Free Product Factors via an Extended Matrix Model

Abstract: A random matrix model for freeness is extended and used to investigate free products of free group factors with matrix algebras and with the hyperfinite II 1 -factor. The latter is shown to be isomorphic to a free group factor having one additional generator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 11 publications
0
99
0
Order By: Relevance
“…An elegant proof of Theorem 5.4.2 for Gaussian matrices which avoid combinatorial arguments appears in [CaC04]. Theorem 5.4.2 was extended to non Gaussian entries in [Dyk93b]. The proof of Theorem 5.4.10 we presented follows the characterization of the law of free unitary variables by a Schwinger-Dyson equation given in [Voi99, Proposition 5.17] and the ideas of [CoMG06].…”
Section: Bibliographical Notesmentioning
confidence: 99%
“…An elegant proof of Theorem 5.4.2 for Gaussian matrices which avoid combinatorial arguments appears in [CaC04]. Theorem 5.4.2 was extended to non Gaussian entries in [Dyk93b]. The proof of Theorem 5.4.10 we presented follows the characterization of the law of free unitary variables by a Schwinger-Dyson equation given in [Voi99, Proposition 5.17] and the ideas of [CoMG06].…”
Section: Bibliographical Notesmentioning
confidence: 99%
“…Let U nc n be the universal C * -algebra generated by the entries of a n×n unitary matrix. By combining the formula U nc n,red ⊗ M n = M n * red C(T) of McClanahan [12] with the formula M n * W * (F s ) = W * (F n 2 s ) ⊗ M n of Dykema [7] we obtain U nc,"…”
Section: Proof (1) Let U V Be the Fundamental Representations Of A mentioning
confidence: 99%
“…Using the matrix model, Voiculescu showed that if (y ij ) 1≤i,j≤N is a * -free family of circular elements in a von Neumann algebra M with respect to a normal faithful state φ, then the matrix y = t k √ 4 − t 2 ) and where u and b are * -free. These and results of a similar nature have been instrumental in applications of free probability to the study of the free group factors L(F n ) and related factors; some of the first of these were [14], [11], [4], [12], [5].…”
Section: Introductionmentioning
confidence: 99%